An in-situ Evaluation Method for the Morphology of Large Format Detector Array. (August 2020) - Huang, Yue; Lin, Chun
Abstract: The morphology, especially the flatness, became more and more crucial for successful flip-chip (FC) bonding for large format detector array. For the first time an in-situ method to evaluate the flatness of bonding samples was established by linking the machine parameter and the sample attribute. The derived collimator correlation was justified by detector array and then it was used as a criterion to examine the accuracy of the bonder's laser leveling module. The combination of the collimator correlation and the laser leveling results could theoretically show more in-situ details of the morphology and can be utilized as either a selection yardstick or a compensation canon before FC bonding. However, whether or not the vacuum system of the bonder had an impact on the morphology could not be decided at present configuration.